2019
DOI: 10.1128/jb.00801-18
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional UDP-Sugar 4-Epimerase Supports Biosynthesis of Multiple Cell Surface Polysaccharides in Sinorhizobium meliloti

Abstract: Sinorhizobium meliloti produces multiple extracellular glycans, including among others, lipopolysaccharides (LPS), and the exopolysaccharides (EPS) succinoglycan (SG) and galactoglucan (GG). These polysaccharides serve cell protective roles. Furthermore, SG and GG promote the interaction of S. meliloti with its host

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…Moreover, c-di-GMP stimulates production of arabinose-containing polysaccharide (APS) and an adhesion polysaccharide of unknown composition, likely similar to A. tumefaciens unipolar adhesion polysaccharide UPP. These polysaccharides facilitate cell aggregation, surface attachment and biofilm formation, however they are not required for effective symbiotic interaction (Pérez-Mendoza et al 2015;Schäper et al 2016;Schäper et al 2019;Xu et al 2012).…”
Section: Regulatory Network Controlling Processes Related To Environmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, c-di-GMP stimulates production of arabinose-containing polysaccharide (APS) and an adhesion polysaccharide of unknown composition, likely similar to A. tumefaciens unipolar adhesion polysaccharide UPP. These polysaccharides facilitate cell aggregation, surface attachment and biofilm formation, however they are not required for effective symbiotic interaction (Pérez-Mendoza et al 2015;Schäper et al 2016;Schäper et al 2019;Xu et al 2012).…”
Section: Regulatory Network Controlling Processes Related To Environmentioning
confidence: 99%
“…Furthermore, at high c-di-GMP levels, S. meliloti produced arabinose-containing polysaccharide (APS) (Figure 3). Its biosynthesis is controlled by the uxs1-uxe-apsS-apsH1-apsE-apsH2 operon (Schäper et al 2019). Expression of the uxs1-aspH2 operon is repressed by MucR and is activated by the cognate transcription regulator CuxR, encoded upstream of the uxs1-apsH2 operon (Schäper et al 2019).…”
Section: Regulation Of Surface Attachment and Biofilm Formation By C-mentioning
confidence: 99%
See 2 more Smart Citations
“…However, also in this case, it is unclear whether the UPP is limited to one of the cell poles and whether it is specially associated with the mother cell. Furthermore, it appears that other polysaccharides might be more important for S. meliloti biofilm formation (Schäper et al 2019). B. abortus cells were shown to produce unipolar adhesins, and strikingly these adhesins were consistently detected at the new pole (Ruiz-Ranwez et al 2013) rather than the old pole, as observed for C. crescentus and H. neptunium.…”
Section: Ctra-dependent Cell Cycle Regulation In Polarly Growing Rhizmentioning
confidence: 92%